From towers to walls: Trump's border wall as entrepreneurial performance - Kolas, Ashild; Oztig, Lacin Ldil (SAGE PUBLICATIONS LTD, 2022)
The pledge to build a great, beautiful southern border wall was a cornerstone of Donald J. Trump's 2016 presidential election campaign. This paper analyzes Trump's border wall project as an example of performative statecraft, suggesting that the wall works better rhetorically, than as a barrier against unauthorized cross-border movement. Identifying Trump's performative statecraft as entrepreneurial, we argue that his border wall discourse differs from that of earlier presidents in the way Trump meshes the performance of the border wall as a protective device with his own performance as an entrepreneur and developer. Trump's border wall discourse accentuates his personal skills as an entrepreneur, and makes these skills relevant to his key campaign promises: to Make America Great Again, and defend the nation against transnational crime. Despite Trump's radical reformulation of US asylum policy, enhanced pursuit of unauthorized immigrants, termination of Obama-era programs like Deferred Action for Childhood Arrivals (DACA), and disturbing but short-lived family separation and 'Zero-Tolerance' detention scheme, the border security policies of President Trump are not as novel as his promotional campaigns would have us believe. In fact, Trump's border control strategies have continued many of the measures introduced by earlier presidents. The novelty of the Trump presidency lies in the strong focus on the new US-Mexico border wall, and fervent attention to the physical attributes and instrumental functions of the wall. Much more than a fence, Trump's proposed border wall is a grand, awe-inspiring monument to national security, and to Trump's entrepreneurial statecraft. It also works as a visual aide for Trump's plan to Make America Great Again. Border walls stand as testimony to the power of the state, and the determination of those who defend it. Trump's border wall would be no exception.
Keywords: US– Mexico border; border walls; performative statecraft; performativity; SECURITY; STATE; GEOGRAPHIES; Environmental Sciences & Ecology; Geography; Public Administration